Analysis of Knowledge Management Implementation at Adhi Karya - Putranto, Brago Adijaya; Bekti, Rudy (The Indonesian Journal of Business Administration, 2013)
As one of the biggest State-Owned Enterprises (SOE) in Indonesia in the field of construction, ADHI's performance always depends on goverment policy. To support governance reform ahead, ADHI saw the opportunity to expand their work into investment, power, and realty. Therefore, ADHI establish new company programs includingÂ the establishment of knowledge management (KM) starting in 2009. This study main purpose is to see how well the implementation of KM in ADHI, and how to develop it better. The quality of KM explored through analyzing ADHI's external and interal organization using PESTEL and McKinsey's 7-S framework to form SWOT Matrix. Zack's KM analysis model later enable to confirm knwoledge gap within the company as the problem to solve. ADHI's new scope of work and poor system information become the main aspects of their knowledge gap cause. ADHI needs to develop short, medium, and long term innitiatives to perfected KM implementation in ADHI. Short-term means to develop system information and training, medium means to develop system to acquire expertise knowledge, and long-term means to expand their expertise in designing and finishing projects.Â Keywords: Knowledge, Human, Information